HUBUNGAN KEBUGARAN JASMANI DENGAN HASIL BELAJAR PJOK SISWA SD NEGRI 101 REJANG LEBONG - Mitha Jacquuelina; Muhammad Supriyadi; Wawan Syafutra (Jurnal Binagogik, 2024)
This research aims to determine the relationship between physical fitness and physical education learning outcomes for students at SD Negeri 101 Rejang Lebong. This research includes correlational research using survey methods and data collection techniques in the form of measurement tests. The subjects in this research were class V students aged 6-12 years at SD Negeri 101 Rejang Lebong with a total of 21 students consisting of 8 male students and 13 female students. The data collection technique uses tests and measurements of physical fitness levels are measured using the TKJI test published by the Ministry of National Education in 2010 which consists of: 60 meter run, 600 run, hanging bent elbows, upright jumping, sitting lying test. This research shows that the level of physical fitness of class V male and female students is classified as poor. Then the average physical fitness test for class V students at SD Negeri 101 Rejang Lebong is 10.95, which is included in the 10-13 interval in the poor category, so it can be said that the physical fitness level of class V students is in the poor category. Meanwhile, to find out the relationship between physical fitness and physical education learning outcomes for class V students, data processing has been carried out using a correlation formula where the correlation coefficient (R test) can be calculated. From the results of data analysis, hypothesis testing and previous discussions, it can be concluded that the analysis results are r < 0.433. Thus, it can be concluded that there is a positive and significant relationship between the level of physical fitness and a significant relationship between the level of physical fitness and the corner learning outcomes of students at SD Negeri 101 Rejang Lebong.